Аз Бога Ведаю: [роман] / Сергей Алексеев - Алексеев Сергей Трофимович (Сокровища Валькирии, 2015)
Экземпляры: ф13; ф14 (201510) / Инвентарный номер: 51548 / Цена: 232.00 / Сис.шифр: Р2 / Авт.знак: А 47 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6